The tectonigral pathway regulates appetitive locomotion in predatory hunting in mice - Meizhu Huang (Nature Portfolio, 2021)
Goal-oriented movement is a fundamental animal behaviour. Here, the authors show that neurons in the superior colliculus project to the substantia nigra pars compacta, regulating dopaminergic signaling and specifically appetitive locomotion in mice.